Design and control of pressure-swing distillation for azeotropes with different types of boiling behavior at different pressures. (June 2016) - Wang, Yinglong; Zhang, Zhen; Xu, Dongfang; Liu, Wei; Zhu, Zhaoyou
Graphical abstract: Highlights: We propose a UPSD for separating a mixture that presents the minimum- and maximum-boiling azeotropes as pressure changes. We give a cascade control structure for base level of the high-pressure column in the UPSD. Dynamic controls of the CSPD with full heat-integration and the UPSD with partial heat-integration are studied. The UPSD has the superiority of good controllability compared to the CPSD. Abstract: The mixture of n -heptane and isobutanol presents minimum- and maximum-boiling azeotropes as the pressure changes. Two different pressure-swing distillation (PSD) processes are available for this mixture if the pressure of the low-pressure column is set as atmospheric. The steady states of the two available PSDs are optimized by minimizing the total annual cost (TAC) following a sequential iterative optimization procedure. On the basis of the steady-state results, the dynamic control of the two available PSDs and a comparison between them are presented. The conventional PSD (CPSD) is more economical but less controllable than the unusual PSD (UPSD), which has seldom been studied in the published literature. These two different PSD processes should be considered for the separation of this type of mixture according to their advantages.